A review of synchrophasor applications in smart electric grid. Issue 3 (21st July 2016) - Lee, H.; Tushar,; Cui, B.; Mallikeswaran, A.; Banerjee, P.; Srivastava, A. K.
Abstract : The adoption of synchrophasor technology with ongoing smart grid activities has resulted in a transformation of the power system monitoring and control practices. Phasor measurement units (PMUs) synchronized by the global positioning system (GPS) provide time‐stamped voltage and current phasors at faster rate for enhanced situational awareness and decision support compared to existing legacy technology and help in improving the reliability of the power system. The measurements from PMU can be used for number of possible applications and can be classified based on the time criticality requirements (e.g., adaptive protection vs state estimation (SE)), control center versus engineering analysis (e.g., state estimation vs model validation), monitoring versus control (e.g., angle monitoring vs stability control), and existing versus evolving (e.g., state estimation vs transient stability) applications. Some of these synchrophasor applications like monitoring and postmortem studies have been already adopted by power industry, some of the synchrophasor‐based control applications are still being investigated. In this study, various power system applications supported by synchrophasor technology are reviewed and discussed. WIREs Energy Environ 2017, 6:e223. doi: 10.1002/wene.223 This article is categorized under: Energy Systems Economics > Systems and Infrastructure Abstract :